A nickel-doped catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202311386691.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-10-23
AI Technical Summary
Existing precious metal catalysts are expensive, while non-precious metal catalysts are prone to sintering and have reduced activity, resulting in low efficiency and short catalyst life in the methane-carbon dioxide dry reforming reaction.
A nickel-doped noble metal supported catalyst is prepared by doping nickel atoms into an oxide support and loading a single-atom metal. The preparation method includes steps such as mixing, drying, and calcination.
It achieves high efficiency in catalytic methane conversion at lower temperatures, reduces the amount of precious metals used, improves resistance to sintering, enhances resistance to carbon deposition, and extends catalyst life.
Smart Images

Figure CN117619402B_ABST
Abstract
Description
Technical Field
[0001] This application relates to a nickel-doped catalyst, its preparation method, and its application, belonging to the field of catalytic materials. Background Technology
[0002] Methane and carbon dioxide are major greenhouse gases, but also abundant and available resources. Dry reforming of methane and carbon dioxide can convert them into useful chemicals or fuels—syngas—helping to reduce carbon emissions, mitigate the greenhouse effect, and promote sustainable development. However, the dry reforming process requires stringent conditions, necessitating the development of efficient, stable, and carbon-resistant catalysts to facilitate the reaction.
[0003] Currently, methane-carbon dioxide dry reforming catalysts are mainly divided into noble metal catalysts and non-noble metal catalysts. Noble metal catalysts are mainly Ru-based, with Rh, Pt, Pd, etc., also used as active components. Their advantages include high reactivity, resistance to sintering, and good resistance to carbon deposition, resulting in a long catalyst life. However, the high price of noble metals limits their large-scale application. Non-noble metal catalysts are mainly nickel-based, with a few using Co, Fe, Mn, etc., as active components. Nickel-based non-noble metal catalysts are inexpensive, but they are prone to sintering during the reaction, leading to a decrease in the number of active sites and specific surface area, resulting in reduced catalyst activity. Furthermore, the enlarged nickel particles resulting from sintering can further lead to deep methane cracking and CO disproportionation, forming a large amount of carbon deposits, further deactivating the catalyst. Therefore, both noble metal and non-noble metal catalysts have their advantages and disadvantages and urgently need improvement. Summary of the Invention
[0004] To combine the advantages of the above two types of catalysts and overcome their respective disadvantages, this invention provides a nickel-doped noble metal supported catalyst.
[0005] According to one aspect of this application, a nickel-doped catalyst is provided, the nickel-doped catalyst comprising an oxide support and nickel atoms doped inside and on the surface of the oxide support;
[0006] In the nickel-doped catalyst, the molar doping amount of nickel atoms is 2-15%;
[0007] The oxide support is selected from at least one of cerium oxide, zirconium oxide, and cerium-zirconium solid solution.
[0008] The oxide support also contains at least one of Pr, Sm, and La in an oxidized state, with a molar content of 0.5-20%.
[0009] The oxide carrier surface is also loaded with a single-atom metal.
[0010] The single-atom metal is selected from at least one of Ru, Rh, Pt, Pd, and Ir;
[0011] In the nickel-doped catalyst, the mass loading of the single-atom metal is 0.005–0.02%.
[0012] According to another aspect of this application, a method for preparing the above-mentioned nickel-doped catalyst is provided, comprising the following steps:
[0013] An aqueous solution containing nickel salt and oxide support precursor is mixed with an alkaline solution, reacted in a sealed container, dried, and calcined to obtain the nickel-doped catalyst.
[0014] The nickel salt is selected from at least one of nickel nitrate, nickel hydrochloride, nickel acetate, and nickel sulfate;
[0015] The oxide support precursor is selected from at least one of cerium nitrate, cerium hydrochloride, cerium acetate, cerium sulfate, zirconium nitrate, zirconium hydrochloride, zirconium acetate, and zirconium sulfate.
[0016] Optionally, the oxide support precursor further contains at least one of the following: praseodymium nitrate, hydrochloride, acetate, sulfate; samarium nitrate, hydrochloride, acetate, sulfate; and lanthanum nitrate, hydrochloride, acetate, sulfate.
[0017] In the aqueous solution containing nickel salt and oxide support precursor, the content of nickel salt is 0.002-1.5 mmol / mL;
[0018] In the aqueous solution containing nickel salt and oxide support precursor, the content of oxide support precursor is 0.1-5 mmol / mL;
[0019] The alkaline solution is selected from at least one of NaOH aqueous solution, KOH aqueous solution, Na2CO3 aqueous solution, Na3PO4 aqueous solution or ammonia solution;
[0020] The concentration of the alkaline solution is 0.3-15 mol / L;
[0021] The mixing process involves stirring at 25–30°C for 0.5–5 hours.
[0022] The reaction temperature is 100–220°C;
[0023] The reaction time is 10–24 hours;
[0024] The drying temperature is 60–150°C;
[0025] The drying time is 8–15 hours;
[0026] The roasting temperature is 400–650°C;
[0027] The roasting time is 2 to 5 hours;
[0028] The roasting atmosphere is an air atmosphere.
[0029] After drying and before roasting, it can be soaked;
[0030] The impregnation process involves immersing the dried product in an aqueous solution containing a single-atom metal precursor, followed by further drying.
[0031] The monatomic metal precursor is selected from at least one of the following: Ru nitrate, hydrochloride, acetate, amino nitrate; Rh nitrate, hydrochloride, acetate, amino nitrate; Pt nitrate, hydrochloride, acetate, amino nitrate; Pd nitrate, hydrochloride, acetate, amino nitrate; and Ir nitrate, hydrochloride, acetate, amino nitrate.
[0032] The aqueous solution containing the single-atom metal precursor has a content of 0.5-30 mg / mL.
[0033] Specifically,
[0034] (1) Dissolve nickel salt and precursor salts of cerium salt, zirconium salt and other elements (at least one of Pr, Sm and La) in water in a certain proportion;
[0035] (2) Add the above metal salt solution dropwise to an alkaline solution of a certain concentration, stir and age at room temperature for 0.5-5 hours to form a precipitate suspension;
[0036] (3) Transfer the precipitate suspension to a hydrothermal reactor and react at 100-220℃ for 10-24 hours;
[0037] (4) Separate the solid, wash it repeatedly with water, and dry it at 60-150℃ for 8-15 hours;
[0038] (5) Immerse the dried solid in a solution prepared in a certain proportion of one or more of the precursor salts such as Ru, Rh, Pt, Pd, and Ir, and dry it at 60-150℃ for 8-15 hours.
[0039] (6) The impregnated solid is calcined in air at 400-650°C for 2-5 hours to obtain a nickel-doped noble metal supported catalyst.
[0040] According to another aspect of this application, an application of the above-described nickel-doped catalyst is provided for catalyzing the dry reforming of methane and carbon dioxide to produce syngas.
[0041] The beneficial effects that this application can produce include:
[0042] 1) The catalyst provided by this invention has a catalytic activity far exceeding that of nickel-based catalysts or single noble metal catalysts, and can achieve a methane conversion rate of over 90% at a relatively low temperature (<550℃);
[0043] 2) The catalyst provided by this invention requires an extremely low loading of precious metals, and its cost is far lower than that of precious metal catalysts;
[0044] 3) The catalyst active sites provided by this invention are all isolated single atoms. Compared with loaded nickel, the anti-sintering ability of doped nickel is greatly enhanced. Noble metals are also not easy to sinter due to low loading.
[0045] 4) The oxygen storage capacity and single-atom distributed active sites on the surface of cerium oxide in the catalyst provided by this invention give the catalyst excellent resistance to carbon deposition. Attached Figure Description
[0046] Figure 1 The graph shows the stability test results of methane-carbon dioxide dry reforming at 550°C for Example 1.
[0047] Figure 2 The image shows the XRD pattern of the catalyst prepared in Example 1.
[0048] Figure 3 The image shows a transmission electron microscope (TEM) image of the catalyst prepared in Example 1, at a scale of 50 nm. Detailed Implementation
[0049] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0050] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0051] Example 1
[0052] Nickel, cerium, zirconium, and Pr nitrates were dissolved in water at a molar ratio of 5:80:10:5, resulting in a concentration of 5 mmol / mL. This metal salt solution was added dropwise to a 4 mol / L alkaline solution and stirred at room temperature for 3 hours to form a precipitate suspension. The precipitate suspension was transferred to a hydrothermal reactor and reacted at 120°C for 18 hours. The resulting solid was separated, repeatedly washed with water, and dried at 80°C for 10 hours. The dried solid was impregnated in a solution of Pt precursor salts prepared at a concentration of 2 mg / mL and dried at 120°C for 8 hours. The impregnated solid was calcined in air at 600°C for 4 hours to obtain a nickel-doped noble metal supported catalyst.
[0053] Figure 2 The image shows the XRD pattern of the catalyst prepared in Example 1.
[0054] Figure 3 The image shows a transmission electron microscope (TEM) image of the catalyst prepared in Example 1, at a scale of 50 nm.
[0055] Depend on Figure 2 , Figure 3 It is evident that the catalyst described in this application was indeed obtained through the method of Example 1.
[0056] Example 2
[0057] Nickel, cerium, zirconium, and Sm nitrates were dissolved in water at a molar ratio of 3:80:15:2, resulting in a concentration of 10 mmol / mL. This metal salt solution was added dropwise to a 2 mol / L alkaline solution and stirred at room temperature for 5 hours to form a precipitate suspension. The precipitate suspension was transferred to a hydrothermal reactor and reacted at 150°C for 24 hours. The resulting solid was separated, repeatedly washed with water, and dried at 80°C for 10 hours. The dried solid was impregnated in a 0.5 mg / mL solution of precursor salts such as Ru and Pt at a molar ratio of 3:1 and dried at 100°C for 12 hours. The impregnated solid was calcined in air at 500°C for 3 hours to obtain a nickel-doped noble metal supported catalyst.
[0058] The characterization results are similar to those of Example 1.
[0059] Example 3
[0060] Nickel was dissolved in water with nitrates of cerium, zirconium, Sm, and La in a molar ratio of 2:80:10:4:4, resulting in a concentration of 0.5 mmol / mL. This metal salt solution was then added dropwise to a 0.3 mol / L alkaline solution and stirred at room temperature for 2 hours to form a precipitate suspension. The precipitate suspension was transferred to a hydrothermal reactor and reacted at 100°C for 10 hours. The resulting solid was separated, repeatedly washed with water, and dried at 60°C for 15 hours. The dried solid was then impregnated in a solution of precursor salts such as Ru, Pd, and Rh in a molar ratio of 1:2:1, with a concentration of 30 mg / mL, and dried at 150°C for 8 hours. The impregnated solid was then calcined in air at 650°C for 2 hours to obtain a nickel-doped noble metal supported catalyst.
[0061] The characterization results are similar to those of Example 1.
[0062] Example 4
[0063] Nickel was dissolved in water with nitrates of cerium, zirconium, Pr, and La in a molar ratio of 4:75:15:3:3, resulting in a concentration of 0.1 mmol / mL. This metal salt solution was then added dropwise to a 0.3 mol / L alkaline solution and stirred at room temperature for 2 hours to form a precipitate suspension. The precipitate suspension was transferred to a hydrothermal reactor and reacted at 170°C for 15 hours. The resulting solid was separated, repeatedly washed with water, and dried at 70°C for 13 hours. The dried solid was then impregnated in a 30 mg / mL solution of precursor salts such as Ru and Rh in a molar ratio of 2:1 and dried at 130°C for 12 hours. The impregnated solid was then calcined in air at 400°C for 5 hours to obtain a nickel-doped noble metal supported catalyst.
[0064] The characterization results are similar to those of Example 1.
[0065] Example 5
[0066] Nickel salt and precursor salts of cerium salt, zirconium salt, and other elements (at least one of Pr, Sm, and La) are dissolved in water in a certain proportion; the above metal salt solution is added dropwise to an alkaline solution of a certain concentration, and stirred and aged at room temperature for 0.5-5 hours to form a precipitate suspension; the precipitate suspension is transferred to a hydrothermal reactor and reacted at 100-220℃ for 10-24 hours; the solid is separated, repeatedly washed with water, and dried at 60-150℃ for 8-15 hours; the dried solid is impregnated in a solution of one or more precursor salts of Ru, Rh, Pt, Pd, and Ir prepared in a certain proportion, and dried at 60-150℃ for 8-15 hours; the impregnated solid is calcined in air at 400-650℃ for 2-5 hours to obtain a nickel-doped noble metal supported catalyst.
[0067] The characterization results are similar to those of Example 1.
[0068] Comparative Example 1
[0069] Cerium, zirconium, and Pr nitrates were dissolved in water at a molar ratio of 80:10:5, with a concentration of 5 mmol / mL. The above metal salt solution was added dropwise to a 4 mol / L alkaline solution and stirred and aged at room temperature for 3 hours to form a precipitate suspension. The precipitate suspension was transferred to a hydrothermal reactor and reacted at 120°C for 18 hours. The resulting solid was separated, repeatedly washed with water, and dried at 80°C for 10 hours. The dried solid was impregnated in a solution of precursor salts such as Ni and Pt, with a Pt concentration of 2 mg / mL and a Ni molar content of 5%, and dried at 120°C for 8 hours. The impregnated solid was calcined in air at 600°C for 4 hours to obtain a nickel-doped noble metal supported catalyst.
[0070] The catalysts obtained in Example 1 and Comparative Example 1 were tested, and the results are shown in Table 1.
[0071] The reforming of methane and carbon dioxide (dry reforming) was carried out in a fixed-bed reactor packed with 50 mg of catalyst and 300 mg of silica sand. A type K thermocouple was inserted into the fixed-bed reactor and brought into contact with the catalyst bed to directly measure the actual temperature of the catalyst during the catalytic process. The reactants (5% methane, 5% carbon dioxide, nitrogen equilibration) were then introduced into the reactor. The methane and carbon dioxide gas mixture had a composition of 1:1. The total flow rate of the gas mixture was 100 mL / min. It flowed from upstream through the catalyst to downstream. Catalytic stability testing was conducted at 550 °C. The composition of the gas leaving the reactor was analyzed by online gas chromatography equipped with a TCD and FID detector.
[0072] Table 1
[0073]
[0074] Figure 1 The graph shows the stability test results of methane-carbon dioxide dry reforming at 550°C for Example 1.
[0075] It can be seen that the catalyst prepared in Example 1 of this application has significantly better performance than the catalyst prepared in Comparative Example 1. The catalysts prepared in Examples 2 to 5 also have similar performance.
[0076] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A nickel-doped catalyst, characterized in that, The nickel-doped catalyst comprises an oxide support and nickel atoms doped inside and on the surface of the oxide support; In the nickel-doped catalyst, the molar doping amount of nickel atoms is 2-15%; The oxide support is selected from at least one of cerium oxide, zirconium oxide, and cerium-zirconium solid solution; The oxide support also contains at least one of Pr, Sm, and La in an oxidized state, with a molar content of 0.5-20%; The oxide carrier surface is also loaded with a single-atom metal. The single-atom metal is selected from at least one of Ru, Rh, Pt, Pd, and Ir; In the nickel-doped catalyst, the mass loading of the single-atom metal is 0.005~0.02%; The nickel-doped catalyst was prepared by a method comprising the following steps: An aqueous solution containing nickel salt and oxide carrier precursor is mixed with an alkaline solution and subjected to hydrothermal reaction at 100-220°C in a sealed container. After drying, the mixture is immersed in an aqueous solution containing a single-atom metal precursor, dried again, and calcined at 400-650°C.
2. A method for preparing the nickel-doped catalyst according to claim 1, characterized in that, Includes the following steps: An aqueous solution containing nickel salt and oxide support precursor is mixed with an alkaline solution and subjected to hydrothermal reaction at 100-220°C in a sealed container. After drying, the mixture is immersed in an aqueous solution containing a single-atom noble metal precursor, dried again, and calcined at 400-650°C to obtain the nickel-doped catalyst.
3. The preparation method according to claim 2, characterized in that, The nickel salt is selected from at least one of nickel nitrate, nickel hydrochloride, nickel acetate, and nickel sulfate; The oxide support precursor is selected from at least one of cerium nitrate, cerium hydrochloride, cerium acetate, cerium sulfate, zirconium nitrate, zirconium hydrochloride, zirconium acetate, and zirconium sulfate. The oxide support precursor also contains at least one of the following: praseodymium nitrate, hydrochloride, acetate, sulfate; samarium nitrate, hydrochloride, acetate, sulfate; and lanthanum nitrate, hydrochloride, acetate, sulfate. In the aqueous solution containing nickel salt and oxide support precursor, the content of nickel salt is 0.002~1.5 mmol / mL; In the aqueous solution containing nickel salt and oxide support precursor, the content of oxide support precursor is 0.1~10 mmol / mL.
4. The preparation method according to claim 2, characterized in that, The alkaline solution is selected from at least one of NaOH aqueous solution, KOH aqueous solution, Na2CO3 aqueous solution, Na3PO4 aqueous solution or ammonia solution; The concentration of the alkaline solution is 0.3~15 mol / L.
5. The preparation method according to claim 2, characterized in that, The mixing process involves stirring at 25-30°C for 0.5-5 hours. The reaction time is 10-24 hours; The drying temperature is 60~150℃; The drying time is 8-15 hours; The roasting time is 2-5 hours; The roasting atmosphere is an air atmosphere.
6. The preparation method according to claim 2, characterized in that, The monatomic metal precursor is selected from at least one of the following: Ru nitrate, hydrochloride, and acetate; Rh nitrate, hydrochloride, and acetate; Pt nitrate, hydrochloride, and acetate; Pd nitrate, hydrochloride, and acetate; and Ir nitrate, hydrochloride, and acetate. The aqueous solution containing the single-atom metal precursor has a content of 0.5~30 mg / mL.
7. An application of the nickel-doped catalyst according to claim 1, characterized in that, Used for catalytic dry reforming of methane and carbon dioxide to produce syngas.
Citation Information
Patent Citations
Catalyst support particle, method of manufacturing the particle and catalyst for purification of exhaust gas
JP2005342554A
Co-precipitated Ni-Ce-ZrO2 catalyst for reformingnatural gas
KR1020040051953A
